Mātava Kōvinta Rāṉaṭē = Madhava Govinda Ranade, a brief sketch of his life - Celvakkēcavarāya Mutaliyār, T., 1864-1921 (SAMP early 20th-century Indian books project, 1920)
On the life of Mahadev Govīnd Ranade, 1842-1901, Judge and social reformer; based on Āmacyā āyushyāntīla k̃āhi āṭhavaṇī, reminiscences of his wife, Ramābāī Rānaḍe, 1862-1924.